Kōmeitō : Politics and Religion in Japan - McLaughlin, Levi, 1972-; Klein, Axel, 1968-; Ehrhardt, George (Book collections on Project MUSE., 2014)
Examines the relationship between religious groups and politics in Japan focusing on Kōmeitō, Japan's most successful religious party. Describes Kōmeitō's campaign practices and varying modes of political participation from its founding to its decision to join the ruling Liberal Democratic Party in a coalition government"